2020
DOI: 10.21831/cp.v39i1.29641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Conditioning on Student Basic Skills Gymnastics

Abstract: Physical conditioning was considered as a strong foundation for developing techniques from different fields. The aims of this study was to determine the impact of physical conditioning in parenting students or athletes gymnastic basic skills. The study was a surveyed research. The study sampling was 82 students aged between 18-19 years from Sport sciences, exactly coaching sciences. Data collection methods used checks and measurements of bio motor and gymnastic fundamental skills. Data analysis using correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…In addition, the daily style of the coaches will also profoundly affect the athletes and stimulate the athletes' training. 13 Many volleyball coaches in China have done just that. They can be strict with themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the daily style of the coaches will also profoundly affect the athletes and stimulate the athletes' training. 13 Many volleyball coaches in China have done just that. They can be strict with themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Tingkat keterampilan gerakan meroda mahasiswa prodi pendidikan jasmani UMPP termasuk kategori baik berarti bahwa mahasiswa sebagian besar mengerti dan menguasai teknik keterampilan gerakan meroda dalam senam lantai. Sukamti, Budiarti, & Nurfadhila (2020) Hasil analisis uji korelasi ganda menjelaskan bahwa terdapat korelasi positif antara kekuatan otot lengan dan power otot tungkai dengan keterampilan gerakan meroda mahasiswa prodi pendidikan jasmani UMPP. Kekuatan otot lengan,power otot tungkai dan keterampilan gerakan meroda mempunyai nilai koefisien korelasi R = 0,739 yang berarti bahwa memiliki derajat korelasi atau tingkat hubungan kategori kuat.…”
Section: Pembahasanunclassified
“…In addition, gymnastics videos available on YouTube and other android applications do not explain the training process to develop basic element models of rhythmic gymnastics with clear motion techniques. The basic element model of rhythmic gymnastics is a game consisting of several disciplines [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the researcher chose to make an application about the basic element model of rhythmic gymnastics based on an android application, which contains basic motion techniques in order to help early age gymnasts and beginners to practice basic techniques with clear motion techniques, to meet the goal of this study. It is also found that there are no previous studies to discuss this topic [15]. Early age is considered the right period to develop children's abilities, while the elementary school period is the key period for the development of basic skills and advanced movement skills [16] particularly to form flexibility and good movements of balancing, jumping and spinning.…”
Section: Introductionmentioning
confidence: 99%